Synthesis and Characterization of Copper(II), Cobalt(II) and Manganese(II) Complexes of 2-(2’-Hydroxynaphthylazo)-5-benzoylbenzimidazole - Devi, T. Chandrika; Krishnan, R.; Salahuddin Kunju, A. (Asian Journal of Chemistry, 2016)
Seven complexes of copper(II) with the ligand 2-(2'-hydroxynaphthyl-azo)-5-benzoylbenzimidazole (NABBI) with the composition [Cu(NABBI)2X2] where X = Cl–, Br–, NO3–, ClO4–, CH3COO–, HCOO– or ½SO42– and nine complexes each of cobalt(II) and manganese(II) having the composition [M(NABBI)2X2] where M = Co(II) or Mn(II) and X = Cl–, Br–, NO3–, ClO4–, CH3COO–, HCOO–, NCS– or ½SO42– have been synthesized and characterized. Systematic analytical methods such as cation-anion estimations, elemental analyses, molar conductance and magnetic susceptibility measurements and IR and UV-Vis spectral studies were made use of in arriving at the conclusions regarding the structure of the complexes. Investigations confirm the identity of the ligands and the distorted octahedral geometry of the complexes studied.